FISCAL-ENVIRONMENTAL LEGISLATION AND SUSTAINABILITY AS A PRINCIPLE IN THE APPLICATION AND INTERPRETATION OF TAX NORMS: ANALYSIS OF ADI NO. 5,553 - Ponzilacqua, Marcio Henrique [UNESP]; Pereira, Flavio Felipe (My University, 2024)
Objective: This article addresses sustainability as a constitutional principle to be followed in the application and interpretation of Brazilian tax legislation. The objective is to verify how the right to an ecologically balanced environment-carved out in article 225 of the Federal Constitution and radiated throughout the Constitutional Text-evidences sustainability as an instrument to achieve the objectives of the Federative Republic of Brazil, so that all national legislation, including taxation, must be applied and interpreted in this scope. Methodology: For the development of the research, the deductive method was used, through a literature review. Structure: To this end, the article is divided into three sections: the first verifies how sustainability is given in the Constitutional Text; the second, how the sustainability paradigm can be applied in tax legislation; and the third examines the judgment of Direct Action of Unconstitutionality No. 5,553, in which the Federal Supreme Court judges the constitutionality of the rules that establish tax benefits for pesticides. The fundamental theoretical framework adopted is that of the Environmental Sociology of Law, which recognizes the complex dynamics of socio-environmentalism in Law, and the methodology used is the case study of the leading case cited, in a propositional approach. Results: It is concluded that sustainability is a constitutional principle and instrument to achieve the objectives of the Republic, and the tax legislation should be applied and interpreted under this focus.
LEGISLAÇÃO FISCAL-AMBIENTAL E A SUSTENTABILIDADE COMO PRINCÍPIO O NA APLICAÇÃO E INTERPRETAÇÃO DAS NORMAS TRIBUTÁRIAS: ANÁLISE DA ADI N.º 5.553
Keywords: Environmental Sociology of Law; Environmental Taxation; Sustainability; Tax Benefits